The Co-Participants Model for Fetal Involvement in Research - Woodward, Leanne (University of Waterloo, 2024)
Research during pregnancy currently lags behind other types of research. Langston (2016) attributes a large portion of this issue to hesitancy by Research Ethics Boards (REBs) to approve research involving pregnant people because it is not always clear how the risks and benefits can be balanced between the parent and fetus when their interests may come in conflict. Authors such as Wild and Biller-Andorno (2016) have emphasized that one major reason that it is difficult to balance these risks and benefits is that the status of the fetus in research is unknown. By answering the question of the status of the fetus in various research contexts, we can reduce the hesitancy of researchers and REBs to pursue and approve research during pregnancy and fill in the gaps in medical knowledge in a safe, ethical manner. I argue that, based on conceptual understandings of terms like “subject” and “participant,” fetuses can fit the role of a research subject when their data is being analyzed for research outcomes, and can therefore be considered participants under the prominent Canadian guidelines known as Tri-Council Policy Statement for Research Involving Humans (TCPS2). Since fetuses are sometimes participants, we should acknowledge them as such when appropriate and take their interests into consideration, while also ensuring that pregnancy alone is not considered a reason to focus on fetal interests. This means protecting fetal interests through proxy consent when the consent process can increase clarity about which role the parent and fetus each play in research, improving respect for the pregnant parent, and welfare for the parent and fetus. I develop the co-participants model for viewing both the pregnant parent and fetus as individual participants who are inextricably linked. This allows researchers to have obligations to the fetus in the same way they would a born child, but to still take these obligations in conjunction with the pregnant parents’ interests and consider how these needs overlap. The co-participants model is preferrable to the “fetus as a patient” model by McCullough and Chervenak (1994, p. 96), and the “double unit” model by Wild (2012, p. 91) because those models use a medical practice definition of patient, and rely on a capacity view of personhood to define participation respectively. Neither model can capture a general descriptive account of what it means to be a participant of research, blurring what that would mean for the fetus. One major objection to the change in fetal status is the perception that it elevates the moral status of the fetus and could affect vital healthcare involving pregnancy termination. The benefit of my co-participants model is that it does not rely on any argument of moral personhood to determine which beings count as participants under the TCPS2. The obligations of the researcher to the fetus begin after the pregnant parent has committed their body to the growth and development of the fetus. In cases where fetuses are imminent to termination, the researcher does not have obligations to protect fetal interests and the fetus is not a participant. The co-participants model for fetal participation is one that can be easily applied to the TCPS2’s current structure and goals, clarifies the role of the parent and fetus in studies with various levels of fetal and parental involvement, and can increase the ability for prospective participants to make informed decisions that are in the best interests of themselves and their fetuses. By using a general definition of participation that does not rely on personhood, the co-participants model ensures that the research status of the fetus does not infringe on the pregnant parent’s autonomy while still ensuring that fetal interests are adequately protected.
Keywords: bioethics; research ethics; feminist ethics; pregnancy; fetal research; fetus